Program Pemulihan Kaum Perempuan Dari Luka Batin Di Gereja Bethel Indonesia Jemaat CBM Ganggeng Raya Tanjung Priok Jakarta Utara - Patintingan, Rima; Iswahyudi, Iswahyudi (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2024)
Women are special creatures in God's eyes. At GBI CBM Ganggeng, women besides giving birth and raising children, serve their husbands and take care of housework, and some have to work to supplement the family's income, some even become the backbone of the family. becomes special because it contains and gives birth to children, who become the forerunners of the church in the future. With so many roles, sometimes there is no time for yourself. What's more, what they do doesn't get the respect it should, women often experience violence in the family, both physically and mentally. Emotional wounds need to be a concern for the church. For this reason, GBI CBM Ganggeng Raya, Tanjung Priok, North Jakarta is holding a recovery program for women from emotional wounds, including personal counseling services, WBI fellowship worship, group prayer (corporate), and MSMEs. Women must continue to be empowered. It is hoped that this journal can inspire Christian women to seek the right help in overcoming their life problems and struggle with God's help to recover from emotional wounds, as well as women and people who interact with individual women to appreciate the roles and functions in their lives. In the end, women can live healthier lives physically and mentally. Wanita adalah makhluk yang istimewa di mata Tuhan. Di GBI CBM Ganggeng, wanita selain melahirkan dan mengasuh anak, melayani suami, mengurus pekerjaan rumah, dan ada yang harus bekerja untuk menambah penghasilan keluarga, bahkan ada yang menjadi tulang punggung keluarga. menjadi istimewa karena mengandung dan melahirkan anak, yang menjadi cikal bakal gereja di masa depan. Dengan begitu banyak peran, kadang tidak ada waktu untuk diri sendiri. Lebih lagi, apa yang dilakukan kurang mendapat penghargaan yang seharusnya. Sering kali wanita mengalami kekerasan dalam keluarga, baik lahir maupun batin. Harga diri perempuan jadi rendah, perempuan merasa tidak berharga. Oleh sebab itu, GBI CBM Ganggeng Raya, Tanjung Priok, Jakarta Utara mengadakan program pemulihan kaum perempuan dari luka batin, mencakup pelayanan konseling pribadi, ibadah persekutuan WBI, doa bersama (korporat), dan UMKM. Berharap melalui jurnal ini dapat menginspirasi perempuan Kristen mau mencari pertolongan yang tepat dalam mengatasi masalah – masalah hidupnya dan berjuang dengan pertolongan Tuhan supaya dipulihkan dari luka batin, serta perempuan dan orang – orang yang berinteraksi dengan individu perempuan untuk menghargai peran - fungsi dalam hidupnya. Pada akhirnya perempuan dapat hidup lebih sehat lahir dan batin.